Digital Enterprise Architecture for Green SPBE in Indonesia - Indri Sudanawati Rozas; Khalid Khalid; Nita Yalina; Noor Wahyudi; Dwi Rolliawati (Universitas Raharja, 2022)
SPBE (Electronic Based Government System) is a legal protection as new breakthroughs in the reform of Indonesian government bureaucracy. The issuance of Presidential Regulation (Perpres) 95/2018 concerning SPBE is expected to be a reference for the transformation from e-Government into i-Government (integrated Government). In the meantime, the government through the Ministry of Administrative and Bureaucratic Reform (PANRB) is drafting an academic paper on the SPBE Bill. Of the 10 elements contained in Presidential Regulation (Perpres) 95/2018, the second element namely SPBE architecture is a concept known in the world of Information Systems as Enterprise Architecture.Enterprise architecture is a conceptual framework that describes how an enterprise is constructed by defining its primary components and the relationships among these components. In SPBE, the main component is defined as domain, consisting of 6 parts, namely: business process architecture domain, data and information, infrastructure, SPBE applications, security, and SPBE services. Unfortunately, the Presidential Regulation (Perpres) 95/2018 has not regulated the concept of Digital Enterprise Architecture, since between Enterprise Architecture (EA) and Digital Enterprise Architecture (DEA) are two things that are significantly different. If EA merely focuses on structuring the company based on the main frame of reference, then DEA focuses on utilizing digital repositories to create living documents as according to the EA framework so that they are easily accessed, modified and managed at any time following the company's development. This study created a DEA model for SPBE in Indonesia. The model created is adapted to the SPBE architecture by carrying out the concept of a digital repository. With digital repositories, time efficiency, paper savings and change management will be easier to achieve. The model created in this study is expected to be utilized to make SPBE much more efficient and green-minded.